Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1212/nxg.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Recessive REEP1 mutation is associated with congenital axonal neuropathy and diaphragmatic palsy

Abstract: Objective:To identify the underlying genetic cause of a congenital neuropathy in a 5-year-old boy as part of a cohort of 32 patients from 23 families with genetically unresolved neuropathies.Methods:We used autozygosity mapping coupled with next-generation sequencing to investigate a consanguineous family from Lebanon with 1 affected and 2 healthy children. Variants were investigated for segregation in the family by Sanger sequencing. A splice site mutation was further evaluated on the messenger RNA level by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
(28 reference statements)
1
12
1
Order By: Relevance
“…To date, only 1 homozygous mutation has been reported in REEP1 ; this affects a splice donor site (p.Phe62Lysfs23*) and was found in a Lebanese patient presenting with a SMARD1-like phenotype which included distal arthrogryposis, congenital axonal neuropathy, hyperreflexia, and respiratory distress, but without any cognitive or language impairment. 4 Although there was a significant phenotypic overlap between this reported individual and our patient, arthrogryposis involving proximal and distal joints was more pronounced in our patient, whereas diaphragmatic palsy seems to be more severe in the homozygous p.Phe62Lysfs23* carrier. In addition, our case adds data on peculiar electromyographic changes that were not reported in the former report.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…To date, only 1 homozygous mutation has been reported in REEP1 ; this affects a splice donor site (p.Phe62Lysfs23*) and was found in a Lebanese patient presenting with a SMARD1-like phenotype which included distal arthrogryposis, congenital axonal neuropathy, hyperreflexia, and respiratory distress, but without any cognitive or language impairment. 4 Although there was a significant phenotypic overlap between this reported individual and our patient, arthrogryposis involving proximal and distal joints was more pronounced in our patient, whereas diaphragmatic palsy seems to be more severe in the homozygous p.Phe62Lysfs23* carrier. In addition, our case adds data on peculiar electromyographic changes that were not reported in the former report.…”
Section: Discussioncontrasting
confidence: 53%
“…6 It has been speculated in a Drosophila model that REEP1 -associated disorders could be ER stress diseases expressing variable phenotypes depending on the type of impaired function in the ER. 4 Furthermore, REEP1 could have a direct role in the control of mitochondrial network morphology through interaction with the crucial protein involved in mitochondrial fission, named DRP1. It has been shown that important alterations take place in the mitochondrial morphology in the primary fibroblasts of patients with REEP1 HSP compared with control cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… One report, however, identified a recurrent heterozygous missense variant (c.386G> C; p.Ser129Thr) in multiple affected individuals from two large unrelated families . Overall, these data lend support to the notion that there are autosomal‐recessive and autosomal‐dominant forms of ERLIN2 ‐related disorders, similar to a small number of other genetic causes of HSP, such as defects in ATL1 (SPG3A), KIF1A (SPG30), KIF1C (SPG58), REEP1 (SPG31), and SPG7 (SPG7) …”
Section: Discussionsupporting
confidence: 52%
“…Several articles in the current issue highlight the role of NGS in this effort. For example, Schottman et al 2 identified REEP1 mutations as the cause of a severe axonal neuropathy with a spinal muscular atrophy with respiratory distress (SMARD) phenotype. This gene was previously associated with a hereditary spastic paraplegia phenotype.…”
mentioning
confidence: 99%